2023
DOI: 10.3390/nu15143097
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Association between Uric Acid and Incident Sarcopenia

Abstract: Background: Sarcopenia has emerged as a significant public health concern. Uric acid (UA), as a metabolite with excellent antioxidant capacity, has been found to be associated with sarcopenia. However, the casual effects of UA on incident sarcopenia still remain unclear. Our study aimed to explore the longitudinal association between UA and incident sarcopenia among middle-aged and older adults. Method: A total of 5086 participants aged ≥45 years old without sarcopenia at baseline were included from the China … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…Moreover, our findings suggested a significant association between LLM and an increased susceptibility to hyperuricemia. This findings aligns with research implemented by Zhou et al ( 34 ), which identified a negative relationship between sarcopenia and uric acid levels in middle-aged and older Chinese individuals. Similarly, two other cross-sectional studies also demonstrated an association between hyperuricemia and reduced skeletal muscle mass ( 35 ) and muscle strength ( 36 ).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, our findings suggested a significant association between LLM and an increased susceptibility to hyperuricemia. This findings aligns with research implemented by Zhou et al ( 34 ), which identified a negative relationship between sarcopenia and uric acid levels in middle-aged and older Chinese individuals. Similarly, two other cross-sectional studies also demonstrated an association between hyperuricemia and reduced skeletal muscle mass ( 35 ) and muscle strength ( 36 ).…”
Section: Discussionsupporting
confidence: 92%